Overstrained Citizens? The Number of Ballot Propositions and the Quality of the Decision Process in Direct Democracy - Alois Stutzer; Michael Baltensperger; Armando N. Meier (Institute of Labor Economics (IZA), 2019)
We study how the number of ballot propositions affects the quality of decision making in direct democracy, as reflected in citizens' knowledge, voting behavior, and attitudes toward democracy. Using three comprehensive data sets from Switzerland with over 3,500 propositions, we exploit variation in the number of federal and cantonal propositions. Voters know the most about the content of federal propositions when they are exclusively presented and less with a high number of concurrent cantonal propositions on the ballot. Across other outcomes we find no consistent indications that â exteuro“ for the observed variation in the exposure to popular votes â exteuro“ a high number of propositions impedes the quality of decision making in Swiss federal direct democracy. In the medium to longer term, more federal propositions on the ballot rather relate to higher perceived political influence and satisfaction with democracy.
Keywords: D03; D72; D78; H00; 330; satisfaction with democracy; political knowledge; pole-party endorsements; political efficacy; direct democracy; ballot length; turnout; voter behavior